Hyperbaric Oxygen Therapy for Venous Leg Ulcers: A 6 Year Retrospective Study of Results of a Single Center - Lalieu, Rutger C.; Akkerman, Ida; van Hulst, Rob A. (Frontiers in Medicine, 2021)
Background: Venous leg ulcers (VLUs) are common and have a large impact on healthcare budgets worldwide. Hyperbaric oxygen therapy (HBOT) may improve healing of these ulcers. Methods: Retrospective, single-center cohort study between 2013 and 2019. All patients with a VLU from an outpatient clinic providing HBOT and wound care were included. The primary outcome measure was wound healing, determined at discharge from the center. Other outcome measures were improvement in patient related outcome measures (PROMs), as assessed by the EQ-5D-3L questionnaire and including quality of life (QoL) and pain score. Results: 59 patients were included, 53% female, with a mean age of 73.4 (± 12.2). Most wounds (83%) had existed longer than three months before starting treatment. Patients received an average of 43 (± 20) sessions of HBOT. After treatment, 37 patients (63%) achieved complete or near-complete wound healing. Wound size decreased from a median of 14 cm2 (interquartile range (IQR) 32 cm2) to 0.5 cm2 (IQR 5.3 cm2), a median decrease of 7.5 (IQR 16.2 cm2) in cm2 (94%). Patients mostly reported improvement for all health aspects on the questionnaire. Pain score decreased from 5.7 (±2.5) to 2.1 (±2.2) (p<0.0001) and health score increased from 57.2 (±15.6) to 69.9 (±18.9) (p=0.02). Conclusions: Patients with non-healing VLUs may benefit from HBOT to achieve complete or substantial wound healing. We recommend a well-designed randomized clinical trial with a number of patients allowing enough statistical power, and of a reasonable duration, to establish the potential of additional HBOT on hard-to-heal venous ulcers.